The Role of Physicians in Hospital Production - Jensen, Gail A.; Morrisey, Michael A. (The Review of Economics and Statistics, 1986)
We use a translog production function approach to examine the effects of medical staff physicians on hospital production, and how their effects differ in teaching and nonteaching hospitals. In teaching hospitals, we also focus on the special role of medical residents. We find that physicians have a strong positive influence on the productivity of other inputs, and that they are substitutes for other resources. Controlling for patient casemix causes significant changes in estimated marginal products; those of labor inputs increase and that of capital declines. The implications of our findings for policy are explored.